Root Canal Configuration of Burmese (Myanmar) Maxillary First Molar: A Micro-Computed Tomography Study - M. M. Kyaw Moe; H. J. Jo; J. H. Ha; S. K. Kim (International Journal of Dentistry)
Aim. To investigate the root canal anatomy of Burmese (Myanmar) permanent maxillary first molar (BMFM) with micro-computed tomography. Methodology. One hundred and one extracted BMFMs were scanned by a SkyScan 1272 scanner (Bruker microCT, Belgium) and reconstructed with NRecon software (Bruker microCT). CTAn software (Bruker microCT) was used to create 3D models of root and internal canal anatomy, while CTVol software (Bruker microCT) was used to visualize 3D models. In each root, Vertucci’s canal types, incidence and location of the lateral canal, incidence, location, and type of isthmus, and number and position of foramina were examined. Results. In 101 specimens, 83 (82.18%) mesiobuccal roots had multiple canals. The most common canal type is type IV (45.5%), followed by type II (17.8%) and I (17.8%) canals. Type III, V, VI, VII, and VIII canals are less than 10% in total. Seven additional canal types were seen for 10% in total. Fourteen (13.86%) distobuccal roots had multiple canals, and the predominant canal type is type I (86.1%), followed by type II (5.9%) and V (4%) canals. Three additional canal types were observed for 4% in total. All palatal roots possessed the simplest type I canal. Apical ramification occurred in 69 mesiobuccal roots (68.3%), 36 distobuccal roots (35.6%), and 37 palatal roots (36.6%). A total of 240 lateral canals were observed in 101 specimens. Each specimen had 2.38 ± 2.22 lateral canals on average. The highest incidence, 136 (56.67%) lateral canals, occurred in the mesiobuccal root, followed by 57 (23.75%) and 47 (19.58%) lateral canals from the distobuccal root and the palatal root, respectively. Each specimen had 6.17 ± 2.42 foramina. Mesiobuccal root had the highest incidence of apical foramina compared to other roots. Seventy-two mesiobuccal roots (71.29%) had isthmus, while only 7 distobuccal roots (6.93%) had isthmus somewhere along the root. Conclusions. The root canal anatomy of BMFM was quite complex, especially in the mesiobuccal root. The predominant canal type was Vertucci type IV in the mesiobuccal root and type I in the distobuccal and palatal roots. In addition, this micro-computed tomography study disclosed complemented canal types and a higher prevalence of lateral canal than the previous studies.